Composite hydrogel dressing as well as preparation method and application thereof
The composite hydrogel dressing formed by cross-linking silk fibroin and sodium alginate, combined with the antibacterial and anti-inflammatory effects of hyperoside, solves the problem of insufficient mechanical strength and adhesion of existing hydrogel dressings on DFU wounds, achieving highly efficient antibacterial and anti-inflammatory effects and a suitable degradation cycle, thus promoting the healing of DFU wounds.
Patent Information
- Application Number
- CN202511749712.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-11-26
- Publication Date
- 2026-02-06
AI Technical Summary
Existing hydrogel dressings are prone to breakage or detachment in active areas, have insufficient adhesion, leading to secondary damage and infection, and have limited antibacterial and anti-inflammatory effects on diabetic foot ulcer (DFU) wounds.
Using silk fibroin and sodium alginate as a mixed solvent, and adding hyperoside, a composite hydrogel dressing is formed through physical cross-linking, which improves mechanical strength and adhesion, and breaks the vicious cycle of infection-inflammation through the antibacterial and anti-inflammatory effects of hyperoside.
It improves the fit between the dressing and the wound, reduces friction damage, enhances antibacterial and anti-inflammatory effects, promotes wound healing, reduces the risk of infection and chronic inflammation, and has an adjustable degradation cycle, reducing the frequency of dressing changes.
Smart Images

Figure CN121466355A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of medical wound dressing technology, and in particular to a composite hydrogel dressing, its preparation method, and its application. Background Technology
[0002] One of the common complications of diabetes is diabetic foot ulcer (DFU). DFU is prone to infection and difficult to cure, and in severe cases it can even lead to amputation. The main goal of DFU treatment is to achieve wound closure as soon as possible. However, high glycemic toxicity, glycation end product toxicity and excessive immune inflammation of the wound seriously hinder the closure of DFU wounds. Among these factors, immune microenvironment disorder is the most important factor in the pathological changes of DFU.
[0003] Clinical treatment of DFU primarily includes glycemic control, wound debridement, wound dressing, pressure modulation, and surgery. Among these, glycemic control has relatively poor timeliness, while debridement, pressure modulation, and surgery require specialized personnel or instruments. Therefore, wound dressing, with its broad applicability, has become a crucial approach to DFU treatment. A major breakthrough in DFU treatment over the past few decades has been the development and application of novel dressings. Ideally, wound dressings should possess properties such as moisture balance, stimulation by active ingredients, antibacterial properties, breathability, and autolytic debridement. In the presence of drug therapy, controlled and continuous drug delivery can further promote granulation tissue formation and epithelial regeneration.
[0004] Due to their excellent biocompatibility, swelling properties, and water retention, hydrogels are considered one of the most promising types of wound dressings. However, existing hydrogel dressings have the following problems: ordinary hydrogels are prone to cracking or falling off when used on active areas (such as joints) due to low mechanical strength, causing secondary damage; insufficient adhesion leads to poor dressing fit, resulting in problems such as exudation and infection; and their effectiveness in simultaneously regulating DFU chronic inflammation and promoting angiogenesis is limited. Summary of the Invention
[0005] The purpose of this invention is to address the above-mentioned problems by providing a composite hydrogel dressing, its preparation method, and its application.
[0006] The first aspect of this invention provides a method for preparing a composite hydrogel dressing, employing the following technical solution:
[0007] A method for preparing a composite hydrogel dressing, wherein the composite hydrogel dressing is obtained by mixing silk fibroin (SF) and sodium alginate (SA) as a mixed solvent, adding hyperoside, mixing, and then casting and curing at a constant temperature to obtain an SF / SA-H hydrogel dressing.
[0008] By employing the above-mentioned technical solutions, both silk fibroin and sodium alginate possess natural biocompatibility. Silk fibroin, derived from silkworm silk, has an amino acid sequence highly similar to human collagen, allowing it to be slowly degraded by the human body with non-cytotoxic degradation products, thus providing a natural "cellular scaffold" for wound healing. Sodium alginate, a natural polysaccharide extracted from brown algae, exhibits excellent hydrophilicity and biodegradability, and is less likely to trigger immune rejection. The cross-linked network formed by the interactions of silk fibroin and sodium alginate through hydrogen bonds and ionic bonds significantly enhances the mechanical strength of the hydrogel, preventing breakage or deformation due to external forces during use. Furthermore, its soft texture and suitable elasticity allow for close contact with the irregular wound surface of DFU wounds, effectively reducing friction between the dressing and the wound. This method avoids secondary trauma caused by traditional dressing changes, improving patient comfort. Sodium alginate itself has antibacterial properties; the carboxyl groups in its molecular chain can inhibit bacterial proliferation by altering bacterial cell membrane permeability. Hypericin, as a natural active ingredient, has significant broad-spectrum antibacterial activity, enhancing its antibacterial effect by disrupting bacterial cell wall structure and inhibiting bacterial DNA replication. Hypericin can also downregulate inflammatory response levels by inhibiting the release of inflammatory factors (such as TNF-α and IL-6), reducing inflammatory symptoms such as redness and exudation at the wound site, breaking the vicious cycle of "infection-inflammation-tissue necrosis," and creating a clean, low-inflammatory microenvironment for wound healing. This enhances the wound healing-promoting effect of hydrogel dressings.
[0009] Preferably, the preparation method includes the following steps:
[0010] S1. Solvent preparation: After the silkworm cocoons are cut into pieces and washed to remove impurities, they are mixed with sodium carbonate solution, boiled to degummify, washed and dried to obtain degummed silk. The degummed silk is placed in lithium bromide solution to dissolve, and after dissolution, it is subjected to dialysis and centrifugation in sequence to finally obtain SF solution, and SA solution is prepared.
[0011] Preparation of S2, SF / SA-H hydrogel dressing: The SF solution prepared in S1 was adjusted to a specific concentration under stable conditions. The SF and SA solutions were mixed and stirred to obtain a mixed solvent. Hypericin was added and stirred to obtain a mixed solution. After mixing evenly, the mixed solution was poured into a mold and cast under constant temperature conditions until the system volume remained unchanged. At this time, calcium chloride solution was added to the mixed system for curing and demolding to obtain the SF / SA-H hydrogel dressing.
[0012] By adopting the above technical solutions, silk fibroin and sodium alginate are mature raw materials that have been widely used in the field of medical dressings. The production process is stable and the cost is controllable. Hypericin is extracted from the traditional medicinal plant St. John's wort, which is abundant and safe. It has been verified by multiple toxicological experiments that it has no acute toxicity. The preparation process of the three materials is simple, using physical cross-linking (such as calcium ion cross-linking) without the need to add chemical cross-linking agents, which further reduces the potential risk of biotoxicity. This dressing meets the therapeutic effect of DFU wound treatment, while having the characteristics of readily available raw materials, convenient production, and high safety. It is easy to realize large-scale production and clinical translation, and has broad prospects for medical application.
[0013] Preferably, in the above preparation method, step S1 specifically comprises:
[0014] S1. Solvent Preparation: After the silkworm cocoons are cut into pieces, they are ultrasonically cleaned for more than 15 minutes to remove impurities. 4.24g of sodium carbonate is added to 2L of water and heated to boiling. After the sodium carbonate is completely dissolved, the silkworm cocoons are put into the sodium carbonate solution and boiled for 60 minutes to degumme. The degummed silk is taken out and washed repeatedly until the degummed silk is clean. It is then placed in an oven to dry for 24 hours to obtain degummed silk. The degummed silk is dissolved in lithium bromide solution. The dissolved silk fibroin is dialyzed in a semi-permeable dialysis bag for 3 days and then centrifuged twice to finally obtain SF solution. The SF solution is stored at 4℃ for later use, and a 2% SA solution is prepared.
[0015] Preferably, in the above preparation method, in step S2, the concentration of SF solution is 2%, and the mixing ratio of SF solution and SA solution is (1-3):(1-3).
[0016] Preferably, in the above preparation method, the mixing ratio of SF solution and SA solution in step S2 is 1:1.
[0017] Preferably, in the above preparation method, in step S2, the molar concentration of hyperoside in the mixture is 0.5–2 mM.
[0018] Preferably, in the above preparation method, in step S2, the molar concentration of hyperoside in the mixture is 1 mM.
[0019] Preferably, in the above preparation method, the constant temperature condition in step S2 is 40°C.
[0020] By adopting the above technical solution and optimizing the steps and parameters of the preparation method, the overall performance of hydrogel dressings can be improved.
[0021] A second aspect of the present invention provides a composite hydrogel dressing prepared by any of the preparation methods described above.
[0022] A third aspect of the present invention provides the use of the above-described composite hydrogel dressing in the preparation of a medicament for promoting the healing of chronic, difficult-to-heal wounds in diabetic patients.
[0023] In summary, this application includes at least one of the following beneficial technical effects:
[0024] 1. Silk fibroin's amino acid sequence is highly similar to that of human collagen, allowing for slow degradation by the body with non-cytotoxic degradation products. It provides a natural "cellular scaffold" for wound healing. Sodium alginate, a natural polysaccharide extracted from brown algae, possesses excellent hydrophilicity and biodegradability, and is unlikely to trigger immune rejection. The hydrogel matrix formed by these two ingredients is soft and elastic, adhering closely to the irregular wound surface of DFU wounds. This effectively reduces frictional damage between the dressing and the wound, avoiding secondary trauma caused by traditional dressing changes and improving patient comfort. Furthermore, this hydrogel is non-allergenic and suitable for continuous care of long-term chronic wounds.
[0025] 2. Sodium alginate has a certain antibacterial ability. The carboxyl group in its molecular chain can inhibit bacterial proliferation by changing the permeability of bacterial cell membranes. Hypericin, as a natural active ingredient, has significant broad-spectrum antibacterial activity. It can enhance the antibacterial effect by destroying the bacterial cell wall structure and inhibiting bacterial DNA replication. At the same time, hypericin can also downregulate the level of inflammatory response by inhibiting the release of inflammatory factors (such as TNF-α and IL-6), reducing inflammatory symptoms such as redness and exudation of the wound, breaking the vicious cycle of "infection-inflammation-tissue necrosis", and creating a clean and low-inflammatory microenvironment for wound healing. The combination of the two achieves the dual effect of "antibacterial + anti-inflammatory", reducing the probability of secondary bacterial infection (especially common pathogens such as Staphylococcus aureus and Escherichia coli) and chronic inflammation in DFU wounds.
[0026] 3. The hydrogel dressing provided by this method has a three-dimensional porous network structure and a water absorption rate of 20-30 times its own weight. It can effectively absorb wound exudate, avoid wound maceration caused by exudate accumulation, and at the same time maintain the wound humidity at the optimal healing range of 40%-60% through the water retention properties of the hydrogel, reduce the crusting caused by wound moisture evaporation, and promote epidermal cell migration.
[0027] 4. The cross-linked network formed by the interaction of silk fibroin and sodium alginate through hydrogen bonds and ionic bonds significantly improves the mechanical strength of the hydrogel, preventing breakage or deformation due to external forces during use. At the same time, by adjusting the compounding ratio of silk fibroin and sodium alginate (preferably 1:1 by mass), the degradation rate of the hydrogel can be precisely controlled. The degradation cycle can match the healing process of DFU wounds (usually 2-4 weeks), ensuring a stable protective barrier for the wound in the early stage of treatment and gradual degradation in the later stage of wound healing. This eliminates the need for frequent dressing changes, reduces medical and nursing operation costs, and avoids interference of residual dressings with newly formed tissues.
[0028] 5. The production processes of silk fibroin and sodium alginate are stable and cost-controllable; hyperoside is extracted from the traditional medicinal plant St. John's wort, which is abundant and safe, and has been verified to have no acute toxicity through multiple toxicological experiments; the preparation process of the three is simple, using physical cross-linking without the need for chemical cross-linking agents, further reducing the potential risk of biotoxicity; this dressing meets the therapeutic requirements of DFU wound treatment while having the characteristics of readily available raw materials, convenient production, and high safety, making it easy to achieve large-scale production and clinical translation, and has broad prospects for medical application. Attached Figure Description
[0029] Figure 1 These are SEM images of the surface structure of the hydrogel dressings obtained in Examples 1-3 of this application, wherein... Figure 1 a is a surface morphology image of SF / SA-3 at a magnification of 500x. Figure 1 b is a surface morphology image of SF / SA-2 at a magnification of 500x. Figure 1 c is the surface morphology of SF / SA-1 at a magnification of 500x. Figure 1 Image d shows the surface morphology of SF / SA-3 at a magnification of 2000x. Figure 1 e is a surface morphology image of SF / SA-2 at a magnification of 2000x. Figure 1 f is a surface morphology image of SF / SA-1 at a magnification of 2000x;
[0030] Figure 2 These are microscopic images of the internal cross-sections of the hydrogel dressings obtained in Examples 1-3 of this application, wherein... Figure 2 a is a microscopic cross-sectional morphology diagram of SF / SA-3. Figure 2 b is a microscopic cross-sectional morphology diagram of SF / SA-2. Figure 2 c is a microscopic cross-sectional morphology diagram of SF / SA-1;
[0031] Figure 3 These are mechanical property test diagrams of the hydrogel dressings obtained in Examples 1-3 of this application, wherein... Figure 3a is a statistical chart of the elongation at break for three types of dressings. Figure 3 b is a statistical chart of the ultimate tensile strength of the three dressings. Figure 3 c shows the stress-strain curves of the three dressings;
[0032] Figure 4 This is a statistical chart of the water vapor transmission rate of the hydrogel dressings obtained in Examples 1-3 of this application;
[0033] Figure 5 This is a statistical chart of the adhesion strength of the hydrogel dressings obtained in Examples 1-3 of this application;
[0034] Figure 6 These are graphs showing the degradation performance test results of the hydrogel dressings obtained in Examples 1-3 of this application, wherein... Figure 6 a is the degradation curve of three hydrogel dressings in PBS solution. Figure 6 b is the degradation curve of three hydrogel dressings in protease degradation solution;
[0035] Figure 7 This is a statistical chart showing the effect of the hydrogel dressings obtained in Examples 2 and 4-6 of this application on cell activity;
[0036] Figure 8 This is a statistical graph showing the changes in wound area in rat experiments using the hydrogel dressing obtained in this application;
[0037] Figure 9 This is a statistical graph showing the HE staining results of the hydrogel dressing obtained in this application in rat experiments. Detailed Implementation
[0038] To make the objectives, technical solutions, and advantages of this invention clearer, the invention will be further described in detail below with reference to embodiments and accompanying drawings. It should be understood that the specific embodiments described herein are merely illustrative and not intended to limit the invention. Modifications or equivalent substitutions made by those skilled in the art based on their understanding of the technical solutions of this invention, without departing from the spirit and scope of the invention, should be covered within the protection scope of this invention.
[0039] The reagents and raw materials used in the following examples are from the following sources:
[0040] Silkworm cocoons: Provided by Southwest University (Chongqing, China).
[0041] Sodium alginate: purchased from Sangon Biotech (Shanghai, China) Co. Ltd.
[0042] Hyperoside: purchased from Beijing Solarbio Science & Technology Co., Ltd.
[0043] Duchenne Modified IoGer medium (DMEM), fetal bovine serum (FBS), and antibiotics (penicillin 10,000 units / ml, streptomycin 10,000 μg / ml) were all obtained from Gibco™ (New York, USA).
[0044] CCK 8 solution and live / dead cell double staining kit: purchased from Beyotime (Shanghai, China).
[0045] In all embodiments, the water used was deionized (DI) water with a resistance of 18.25 MΩ·cm.
[0046] Unless otherwise specified, all reagents, instruments and equipment are commercially available products. For other unspecified conditions, follow the standard conditions or the manufacturer's recommendations.
[0047] The chemical abbreviations and their definitions in this application are as follows:
[0048] Silk fibroin (SF); Sodium alginate (SA); Hyperoside (H); Hydrogel containing silk fibroin and sodium alginate (SF / SA); Silk fibroin / sodium alginate hydrogel loaded with hyperoside (SF / SA-H); Others not specified are subject to industry-standard understanding.
[0049] I. Preparation Example
[0050] Preparation Example 1
[0051] This preparation example provides a method for preparing silk fibroin solution: After the silkworm cocoons are cut into pieces, they are ultrasonically cleaned for at least 15 minutes to remove impurities. 2L of deionized water is measured, 4.24g of sodium carbonate is added, and the mixture is heated to boiling at 100.00℃. After the sodium carbonate is completely dissolved, the silkworm cocoons are placed in the mixture and stirred for 60 minutes. The degummed silk is then removed, thoroughly washed and rubbed with deionized water, and the washing is repeated until the degummed silk is clean. The silk is then placed in a drying oven and dried for 24 hours to obtain degummed silk.
[0052] Lithium bromide solution was prepared by adding 9.6925 g of lithium bromide to 12 mL of pure water. The solution was then added to 3 g of dried silk and dissolved in an oven at 60 °C for 4 hours. The dissolved silk fibroin was dialyzed in a semi-permeable dialysis bag (molecular weight cutoff = 14,000 Da) for 3 days and then centrifuged twice (9000 prm, 4 °C, 20 minutes each time) to obtain a silk fibroin solution. The obtained silk fibroin solution was stored at 4 °C for later use.
[0053] Preparation Example 2
[0054] This preparation example provides a method for preparing sodium alginate solution: 1g of sodium alginate powder is placed in 50mL of deionized water and stirred for 24 hours to dissolve, resulting in a 2% sodium alginate solution.
[0055] II. Implementation Examples
[0056] Example 1
[0057] This embodiment provides a method for preparing SF / SA hydrogels, including the following steps:
[0058] Using the SF solution and SA solution from the preparation example, the concentration of the SF solution was adjusted to 2% under stable conditions. 5 mL of SF solution and 15 mL of SA solution were mixed and placed into a rectangular mold (4 cm * 5 cm) and placed at a constant temperature of 40°C for casting until the volume of the entire system no longer changed. At this point, 1 mL of 2% w / w calcium chloride solution was added to the mixture for curing and demolding to obtain the SF / SA hydrogel, denoted as SF / SA-1.
[0059] Example 2
[0060] A method for preparing SF / SA hydrogel differs from Example 1 in that the amount of SF solution used is 10 mL and the amount of SA solution used is 10 mL, and the hydrogel obtained is denoted as SF / SA-2.
[0061] Example 3
[0062] A method for preparing SF / SA hydrogel differs from Example 1 in that the amount of SF solution used is 15 mL and the amount of SA solution used is 5 mL, and the hydrogel obtained is designated as SF / SA-3.
[0063] Example 4
[0064] A method for preparing a composite hydrogel dressing includes the following steps:
[0065] S1. Solvent preparation: SF solution and SA solution prepared using the preparation example.
[0066] Preparation of S2, SF / SA-H hydrogel dressing: The SF solution prepared in S1 was adjusted to a concentration of 2% under stable conditions. The SF and SA solutions were mixed in a 1:1 ratio (i.e., 10mL:10mL) and stirred to obtain a mixed solvent. At the same time, 4.644mg of hyperoside was added and stirring was continued to obtain a mixed solution. At this time, the molar concentration of hyperoside in the mixed solution was 0.5mM. After mixing evenly, the mixed solution was placed in a rectangular mold (4cm*5cm) and placed in a constant temperature environment of 40℃ for casting until the volume of the entire system no longer changed. At this time, 1mL of calcium chloride solution with a concentration of 2% w / w was added to the mixed system for curing and demolding to obtain the SF / SA-H hydrogel dressing.
[0067] The hydrogel dressing prepared in this embodiment is designated as SF / SA-H1.
[0068] Example 5
[0069] A method for preparing a composite hydrogel dressing differs from Example 4 in that the amount of hyperoside added in S2 is 9.288 mg, and the molar concentration of hyperoside in the mixture is 1 mM; the rest is the same as in Example 4, and the resulting hydrogel dressing is denoted as SF / SA-H2.
[0070] Example 6
[0071] A method for preparing a composite hydrogel dressing differs from Example 4 in that the amount of hyperoside added in S2 is 18.576 mg, and the molar concentration of hyperoside in the mixture is 2 mM; the rest is the same as in Example 4, and the resulting hydrogel dressing is denoted as SF / SA-H3.
[0072] Example 7
[0073] A method for preparing a composite hydrogel dressing differs from Example 4 in that the amount of SF solution used is 5 mL and the amount of SA solution used is 15 mL, while the rest is the same as in Example 4. The resulting hydrogel dressing is denoted as SF / SA-H4.
[0074] Example 8
[0075] A method for preparing a composite hydrogel dressing differs from Example 4 in that the amount of SF solution used is 15 mL and the amount of SA solution used is 5 mL, while the rest is the same as in Example 4. The resulting hydrogel dressing is denoted as SF / SA-H6.
[0076] III. Performance Test Experiments and Results
[0077] 1. Structural characterization
[0078] The hydrogel dressings prepared in Examples 1-3 were freeze-dried and sputter-coated with gold. The surface and cross-sectional morphology of the dressings with different SF / SA blend ratios were analyzed by field emission scanning electron microscopy (FE-SEM) (Sigma 300, ZEISS, Germany) at accelerating voltages of 6 kV and 4 kV, respectively.
[0079] The microstructure of the hydrogel dressing was examined using a scanning electron microscope (SEM). Before the examination, the hydrogel dressing was vacuum dried at room temperature, cut into 1cm × 2cm rectangular samples, sputter-coated with gold, fixed on the scanning base, and the micromorphology of its surface and cross-section was observed under SEM. The micromorphology of SF / SA-3, SF / SA-2 and SF / SA-1 was observed at different magnifications. The surface roughness and the layered structure of the porous network in the cross-section of the dressing were also observed.
[0080] Structural characterization such as Figure 1 and Figure 2 As shown, where, Figure 1 This is a surface morphology image of the sample. Figure 1 a is a surface morphology image of SF / SA-3 at a magnification of 500x. Figure 1 b is a surface morphology image of SF / SA-2 at a magnification of 500x. Figure 1 c is the surface morphology of SF / SA-1 at a magnification of 500x. Figure 1 Image d shows the surface morphology of SF / SA-3 at a magnification of 2000x. Figure 1 e is a surface morphology image of SF / SA-2 at a magnification of 2000x. Figure 1 f is a surface morphology image of SF / SA-1 at a magnification of 2000x.
[0081] Figure 2 a is a microscopic cross-sectional morphology diagram of SF / SA-3. Figure 2 b is a microscopic cross-sectional morphology diagram of SF / SA-2. Figure 2 c is a microscopic cross-sectional morphology diagram of SF / SA-1.
[0082] Microscopic comparison reveals that as the SA content increases, surface cracks disappear, fiber streaks decrease, and surface smoothness improves in SF / SA samples. This suggests that the introduction of SA can effectively function as a stabilizer.
[0083] The internal cross-sectional microstructure of SF / SA shows that, under the action of CaCl2, the two types of fibers, SF and SA, in SF / SA interact and combine with each other, forming a layered structure of porous network inside. At the same time, as the composition ratio of SF / SA in the sample increases, the pore size of the sample generally shows a decreasing trend, while the pore morphology and arrangement show a more uniform and compact trend.
[0084] 2. Mechanical property testing
[0085] The mechanical properties of the hydrogel dressings prepared in Examples 1-3 were tested using the ASTM-D882 standard method. Stress-strain curves of the samples (5 cm × 1 cm) were measured using a universal testing machine (model E43-104) from MTS Corporation, equipped with a 10 N load cell, at a rate of 2 mm / min. The ultimate tensile strength (UTS) and elongation at break (EB) and other mechanical parameters of the dressings were automatically obtained using the accompanying software.
[0086] Test results are as follows Figure 3 As shown, where, Figure 3 a is a statistical chart of the elongation at break for three types of dressings. Figure 3 b is a statistical chart of the ultimate tensile strength of the three dressings. Figure 3 Figure c shows the stress-strain curves of the three dressings. As can be seen from the figure, with the increase of SA content, the EB value shows a significant upward trend, and the ultimate tensile strength is significantly improved. This indicates that the introduction of SA can effectively improve the flexibility of SF / SA, making the dressing more resistant to torsional deformation. However, there is no significant difference in the UTS values between SF / SA-3 and SF / SA-2, indicating that SF can impart rigidity to SF / SA within certain limits, making the dressing more resistant to tensile deformation. This trend may be due to changes in the β-sheet structure that determines the mechanical properties of SF-based materials in SF / SA, as well as the different degrees of SA crosslinking in the materials. SF / SA with higher SF content has a higher proportion of β-sheet conformation, resulting in a higher packing density of the layered structure inside the dressing, leading to increased rigidity. Furthermore, with the increase of SA content in SF / SA, the degree of crosslinking of its internal fibers also increases, thus enhancing the flexibility of SF / SA. This result indicates that changes in the SF / SA ratio in SF / SA may affect the synergistic effect of the two polymers on SF / SA, thereby altering the mechanical properties of SF / SA.
[0087] 3. Breathability test
[0088] The water vapor transmission rate (WVTR) of the SF / SA dressing was characterized according to ASTM E96. The procedure was as follows: A circular dressing sample was placed over the mouth of a wide-mouth bottle (3.5 cm inner diameter) containing physiological saline. The entire setup was kept at a constant temperature of 37°C and 50±5% relative humidity (RH). The amount of water vapor transmitted through the sample was calculated by measuring the mass loss of the bottle. The water vapor transmission rate (g / (m²·24 h)) was calculated by dividing the daily weight loss by the bottle opening area, as shown in the following formula:
[0089]
[0090] Where W0 represents the initial mass of the system (g), W1 represents the final mass of the system (g), and s represents the opening area (m²). 2 ), t represents the test time, and the unit of WVTR is g / (m²·24 h).
[0091] The test results of the three dressings are as follows: Figure 4 As shown, the optimal WVTR for skin wound dressings should be between 2000-2500 g*m. -2 *day - The WVTR values are between 1 and 1; this is because when wound tissue exchanges gases with the external environment at this rate, it can maintain a properly moist microenvironment on the wound surface to promote tissue repair and reconstruction, while also effectively preventing excessive drying and dehydration of the wound surface. Comparison revealed that the WVTR values of SF / SA-2 and SF / SA-1 samples met this condition, enabling them to provide good moisture permeability to wound tissue and promote wound healing.
[0092] 4. Adhesion testing
[0093] The adhesive properties of the dressing samples prepared in Examples 1-3 under wet conditions were determined using a universal testing machine (ETS-E43-104, MTS Corporation, USA) according to the methods described in the literature. Brief procedure: The prepared dressings were cut into 10 mm × 10 mm square specimens and clamped between pigskin to ensure a constant contact area. Before testing, the samples were immersed in PBS solution and treated at 37°C for 20 minutes. The test was conducted at a tensile rate of 1.0 mm / min until the sample failed. The adhesive strength was calculated using the following formula:
[0094]
[0095] Where F is the maximum load (N), and S is the bonding area (m²). 2 The unit of adhesion strength P is (kPa).
[0096] The results are as follows Figure 5 As shown.
[0097] 5. Degradation performance (determination of mass loss rate in PBS solution)
[0098] The degradation behavior of the prepared dressing samples was assessed by immersion in PBS and enzyme solutions. Appropriate degradation of the wound dressing during wound healing not only promotes tissue remodeling but also enables the targeted and sustained release of bioactive substances from the dressing to the wound site.
[0099] Specific procedures: Dissolve Protease XIV powder (protease inhibitor) in PBS solution to prepare a protease degradation solution with a concentration of 3 units / ml. After lyophilizing the three different SF / SA hydrogel dressings prepared in Examples 1-3, weigh and record the weight. Take 150mg of each dressing and immerse it in 2ml of the prepared protease degradation solution and PBS solution respectively, and incubate in a shaker at 37°C. Every two days, collect the sample residues after degradation, wash them, lyophilize them, weigh and record the weight. The degradation behavior of the sample is represented by dividing the remaining mass each time by the initial mass. Repeat the above operation until the sample is completely degraded.
[0100] The results are as follows Figure 6 As shown, where, Figure 6 a is the degradation curve of three hydrogel dressings in PBS solution. Figure 6 Figure b shows the degradation curves of the three hydrogel dressings in the protease degradation solution. The first degradation curve shows that all three different SF / SA materials exhibit excellent stability in PBS solution. This degradation result is consistent with previous studies, indicating that both silk fibroin and sodium alginate can be stably present in PBS solution. The second curve... Figure 3 The degradation curves show that all samples exhibited a relatively sensitive and specific degradation response to PBS containing Protease XIV. The sample with the highest SF content showed the strongest degradation behavior. The reason for the difference may be that SF contains more Protease XIV binding sites, which leads to the faster degradation of SF in AFAD. SA, as a polysaccharide, may not have a receptor that specifically binds to Protease XIV, thus preventing its degradation.
[0101] For drug-loaded wound dressings, rapid or insignificant degradation rates will be detrimental to the sustained release of drugs in the scaffold, and SF / SA-2 samples exhibiting moderate degradation behavior may be the preferred material for wound dressings.
[0102] As shown in performance testing experiments 1-5, the SF / SA samples SF / SA-1, SF / SA-2, and SF / SA-3, prepared with three different SF / SA ratios, exhibit significant differences in certain properties. From an overall perspective, the SF / SA-2 sample possesses the most comprehensive properties for wound dressing among the three, such as mechanical properties similar to human skin, strong skin adhesion, and suitable breathability and degradability. Therefore, it is proposed that the optimal SF to SA ratio in SF / SA be 1:1, and the SF / SA-2 sample with the optimal SF / SA ratio (i.e., the hydrogel dressings obtained in Examples 4-6) will be used as a representative sample in the following biological activity evaluation.
[0103] 6. Cell compatibility evaluation
[0104] According to ISO 10993-5 standard, cell viability in the presence of samples was detected using the Cell Count Kit-8 (CCK-8) method. NIH3T3 fibroblasts at a density of 8×10³ cells / well were seeded into 96-well plates and pre-cultured for 12 hours in DMEM medium containing 10% fetal bovine serum (FBS) and 1% antibiotics at 37°C and 5% CO2.
[0105] The sample extract was then replaced with a normal culture medium solution (prepared by soaking the hydrogel dressing sample material prepared in Examples 4-6 in normal culture medium for 12 hours), and cultured for 12, 24, and 36 hours respectively. At each time point, the extract was replaced with 100 μL of normal culture medium containing 10% CCK8 reagent, and incubated in the dark for 1 hour. The absorbance at 450 nm was immediately measured using a MultiskanGo microplate reader from Thermo Fisher Scientific, USA.
[0106] The formula for calculating cell viability is as follows:
[0107] Cell viability (%) = [(Asample - Ablank) / (Acontrol - Ablank)] × 100%
[0108] Where Asample represents the absorbance value of the test sample, Acontrol represents the absorbance value of the control group (Example 2), and Ablank represents the absorbance value of the blank group.
[0109] Cell viability results as follows Figure 7 As shown in the figure, comparing the cell viability values of cells cultured in normal complete culture medium and those cultured in drug-free SF / SA soaking solution revealed no significant difference between the two values at any time point. This indicates that the prepared dressing base membrane without bioactive drugs had no adverse effect on cell growth. After incubation with different concentrations of hyperoside in SF / SA-2 for 12, 24, and 36 hours, the cell viability of all groups exceeded 80%, and cell viability increased with increasing hyperoside concentration. When the concentration reached 2 mM, the survival rate reached approximately 125%, indicating that hyperoside can promote cell proliferation.
[0110] 7. Animal experiments
[0111] A series of experiments were conducted using male SD rats produced by SPF (China) Biotechnology Co., Ltd., weighing between 180 and 230 g. The animal experiments were approved by the Research Ethics Committee of Chongqing Medical University (Chongqing, China) and were conducted in accordance with the guidelines for the care and use of laboratory animals as specified in the National Institutes of Health (NIH) guidelines. All rats were fed and maintained in a room with a 12-hour light / dark cycle and stable temperature (25°C) and humidity.
[0112] SD rats were fed a high-sugar, high-fat diet for 4 weeks, followed by intraperitoneal injections of 50 mg / kg STZ solution every three days. A diabetic model was considered successfully established when blood glucose levels were ≥16.8 mmol / L, accompanied by overeating symptoms, weight loss, and increased urination. Under general anesthesia, a 7 mm diameter deep full-thickness skin defect was carefully created in the paw using a skin biopsy punch.
[0113] Rats were then assigned to four treatment groups: in the blank control group, no dressing was applied; in the commercial group, the wound was treated with 3M hydrocolloid dressing; in the SF / SA-2 group, the wound was treated with SF / SA-2 composite hydrogel; and in the SF / SA-H2 group, the wound was covered with SF / SA-H2 and then secured with a regular bandage. All dressings were changed every two days.
[0114] Rats were housed in an environment with a precisely regulated 12-hour light / dark cycle and consistent temperature (25°C) and humidity. Postoperative skin healing was evaluated and photographed on days 4, 8, 12, and 16 of the procedure. Euthanasia was performed by injection of sodium pentobarbital when necessary. Rats were sacrificed on days 4, 8, 12, and 16 postoperatively, and full-thickness skin wounds and subcutaneous tissue specimens were collected. After fixation in 4% paraformaldehyde solution, sections were stained, embedded in paraffin, and analyzed using routine hematoxylin-eosin (HE) staining. All stained sections were observed under an optical microscope (UB203, UOP, China).
[0115] Wound area diagram as shown Figure 8 As shown in the figure, the staining results of the sections are as follows. Figure 9 As shown in the images, based on the wound area diagram and HE staining of tissue sections, the wound treated with SA / SA-H2 healed the fastest, followed by 3M commercial dressing. This indicates that the drug hyperoside promotes the healing of diabetic foot ulcers and shortens the healing time.
[0116] In summary, the hydrogel dressing provided by this method, with sodium alginate and silk fibroin as the matrix, is soft and has suitable elasticity, closely adhering to the irregular wound surface of DFU wounds. This effectively reduces frictional damage between the dressing and the wound, avoids secondary trauma caused by traditional dressing changes, and improves patient comfort. Simultaneously, the combination of sodium alginate and hyperoside achieves a dual effect of "antibacterial + anti-inflammatory," reducing the probability of secondary bacterial infections (especially common pathogens such as Staphylococcus aureus and Escherichia coli) and chronic inflammation in DFU wounds. By adjusting the mixing ratio of silk fibroin and sodium alginate (preferably 1:1 by mass), the hydrogel can be achieved. Precise control of the degradation rate, with a degradation cycle that matches the DFU wound healing process (typically 2-4 weeks), ensures a stable protective barrier for the wound in the early stages of treatment while gradually degrading in the later stages of wound healing. This eliminates the need for frequent dressing changes, reducing medical and nursing costs, and avoids interference from residual dressings on newly formed tissues. The preparation process is simple, employing physical cross-linking without the need for chemical cross-linking agents, further reducing potential biotoxicity risks. This dressing not only meets the therapeutic efficacy requirements of DFU wound treatment but also features readily available raw materials, convenient production, and high safety, making it easy to achieve large-scale production and clinical translation, and possessing broad prospects for medical applications.
Claims
1. A method for preparing a composite hydrogel dressing, characterized in that: The composite hydrogel dressing is an SF / SA-H hydrogel dressing obtained by mixing silk fibroin (SF) and sodium alginate (SA) as a mixed solvent, adding hyperoside, and then casting and curing at a constant temperature and demolding.
2. The preparation method according to claim 1, characterized in that: Includes the following steps: S1. Solvent preparation: After the silkworm cocoons are cut into pieces and washed to remove impurities, they are mixed with sodium carbonate solution, boiled to degummify, washed and dried to obtain degummed silk. The degummed silk is placed in lithium bromide solution to dissolve, and after dissolution, it is subjected to dialysis and centrifugation in sequence to finally obtain SF solution, and SA solution is prepared. Preparation of S2, SF / SA-H hydrogel dressing: The SF solution prepared in S1 was adjusted to a specific concentration under stable conditions. The SF and SA solutions were mixed and stirred to obtain a mixed solvent. Hypericin was added and stirred to obtain a mixed solution. After mixing evenly, the mixed solution was poured into a mold and cast under constant temperature conditions until the system volume remained unchanged. At this time, calcium chloride solution was added to the mixed system for curing and demolding to obtain the SF / SA-H hydrogel dressing.
3. The preparation method according to claim 2, characterized in that: S1. Solvent Preparation: After the silkworm cocoons are cut into pieces, they are ultrasonically cleaned for more than 15 minutes to remove impurities. 4.24g of sodium carbonate is added to 2L of water and heated to boiling. After the sodium carbonate is completely dissolved, the silkworm cocoons are put into the sodium carbonate solution and boiled for 60 minutes to degumme. The degummed silk is taken out and washed repeatedly until the degummed silk is clean. It is then placed in an oven to dry for 24 hours to obtain degummed silk. The degummed silk is dissolved in lithium bromide solution. The dissolved silk fibroin is dialyzed in a semi-permeable dialysis bag for 3 days and then centrifuged twice to finally obtain SF solution. The SF solution is stored at 4℃ for later use, and a 2% SA solution is prepared.
4. The preparation method according to claim 3, characterized in that: In S2, the concentration of SF solution is 2%, and the mixing ratio of SF solution and SA solution is (1-3):(1-3).
5. The preparation method according to claim 2, characterized in that: In S2, the mixing ratio of SF solution and SA solution is 1:
1.
6. The preparation method according to claim 2, characterized in that: In S2, the molar concentration of hyperoside in the mixture is 0.5–2 mM.
7. The preparation method according to claim 2, characterized in that: In S2, the molar concentration of hyperoside in the mixture is 1 mM.
8. The preparation method according to claim 2, characterized in that: In S2, the constant temperature condition is 40℃.
9. A composite hydrogel dressing, characterized in that: It is prepared by the preparation method according to any one of claims 1-8.
10. The use of the composite hydrogel dressing according to claim 9 in the preparation of a medicament for promoting the healing of chronic, difficult-to-heal wounds in diabetic patients.